Nilai-Nilai Pendidikan Akhlak Ali Bin Abi Thalib Dan Relevansinya Terhadap Tujuan Pendidikan Islam - Waluyo Erry Wahyudi; Agus Faisal Asyha; Asti Murniasih (Journal Khafi : Journal Of Islamic Studies, 2024)
This research is a literature study using a historical approach. The historical approach used in this study focuses on biographies related to the life records of Ali bin Abi Talib to find out the background of the character's life and his socio-political environment. The data collection procedure used is documentation. While the data analysis technique uses content analysis techniques. The results of this study indicate that the moral education values ​​of Ali bin Abi Talib contained in the biography of Ali bin Abi Talib by Ali Muhammad Ash-Shallabi namely Ali bin Abi Talib has broad knowledge and deep understanding of his religion, Ali bin Abi Talib was an ascetic person , humble, generous, ashamed of Allah, and fair and not favoritism. The conclusion of this study is that the moral education values ​​of Ali bin Abi Talib in the biography of Ali bin Abi Talib by Muhammad Ash-Shallabi are relevant to the goals of Islamic education. The moral education values ​​of Ali bin Abi Talib in the biography of Ali bin Abi Talib by Muhammad Ash-Shallabi have six noble morals that are in accordance with the goals of Islamic education.